Effects of parent and child behaviours on overweight and obesity in infants and young children from disadvantaged backgrounds: systematic review with narrative synthesis - Catherine Georgina Russell; Sarah Taki; Rachel Laws; Leva Azadi; Karen J. Campbell; Rosalind Elliott; John Lynch; Kylie Ball; Rachael Taylor; Elizabeth Denney-Wilson (BMC, 2016)
Abstract Background Despite the crucial need to develop targeted and effective approaches for obesity prevention in children most at risk, the pathways explaining socioeconomic disparity in children's obesity prevalence remain poorly understood. Methods We conducted a systematic review of the literature that investigated causes of weight gain in children aged 0-5 years from socioeconomically disadvantaged or Indigenous backgrounds residing in OECD countries. Major electronic databases were searched from inception until December 2015. Key words identified studies addressing relationships between parenting, child eating, child physical activity or sedentary behaviour and child weight in disadvantaged samples. Results A total of 32 articles met the inclusion criteria. The Mixed Methods Appraisal Tool quality rating for the studies ranged from 25 % (weak) to 100 % (strong). Studies predominantly reported on relationships between parenting and child weight (n = 21), or parenting and child eating (n = 12), with fewer (n = 8) investigating child eating and weight. Most evidence was from socio-economically disadvantaged ethnic minority groups in the USA. Clustering of diet, weight and feeding behaviours by socioeconomic indicators and ethnicity precluded identification of independent effects of each of these risk factors. Conclusions This review has highlighted significant gaps in our mechanistic understanding of the relative importance of different aspects of parent and child behaviours in disadvantaged population groups.